The seventh century in Byzantine-Muslim relations: Characteristics and forces - Sahas, Daniel J. (Islam and Christian-Muslim relations, 1991)
The seventh century Muslim-Byzantine relations are revealing and paradigmatic of the political, religious and "national" forces (Persian, Greek and Arab), each striving to dominate the land and the heart of the region. Notwithstanding the deeply-rooted Christian tradition, orthodox or heretical, among the populations of the Byzantine (Eastern Roman) empire, integrally Arab in temperament and Greek in appearance, the Muslim expansion outside the "island" of Arabia proper must be seen as part of a larger phenomenon of rising Arab, rather than Muslim solidarity and self-consciousness; thence the unique, in many ways, character and content of the interaction of the Christian and Muslim community. The theological divisions alone among the Christian population do not explain the successful expansion of Islam; they underline the dynamics and the characteristics of the seventh century.